Otologic and audiologic characteristics of children with skeletal dysplasia in central China. (July 2013) - Chen, Guanming; Fu, Siqing; Dong, Jiashu; Zhang, Li
Abstract Conclusion: Otologic and audiologic abnormalities are both highly prevalent in Chinese children with skeletal dysplasias. Audiologic and otologic evaluations with medical intervention are recommended for these children. Objective: Children with skeletal dysplasia have a number of otolaryngologic issues including hearing loss. This study aimed to investigate the otologic and audiologic features of Chinese children with skeletal dysplasia in central China. Methods: Otologic evaluations and pure tone audiometry were performed in children with skeletal dysplasias. To explore the potential associations with hearing loss, we studied various craniofacial anomalies. Results: A total of 125 children (mean age 9.2 years, range 5–18 years) with skeletal dysplasia were enrolled, and otoscopic examination identified eardrum abnormalities in 45.6% of the children. Audiologic analysis revealed 14 cases (11.2%) with conductive hearing loss (CHL) and 22 cases (17.6%) with sensorineural hearing loss (SNHL).